Visual Thinking, game-based learning and digital Quiz as strategy of mathematics comprehension - Moral-Sánchez, Silvia Natividad; Roldán-Ortiz, Rocio (My University, 2022)
Personalisation in education is key to developing learning strategies in the new educational paradigm. Placing the student at the centre of the teaching-learning process makes this personalisation possible, involving not only students, encouraging their motivation and creativity, but also teachers who can change traditional methodologies with the use of active methodologies far from teaching only purely academic content. The design of activities should be based on the students' interest, encouraging their imagination and motivation in order to make comprehensive learning possible. Given that most of the comprehension problems in the subject of mathematics are due to the lack of use or incorrect use of resources, materials or traditional methodologies by teachers, which prevent the achievement of learning, it is necessary to bring about this change. Moreover, the interdisciplinary nature of the teaching proposals with content from other subjects enriches the whole process and, thanks to ICT, they are integrated, thus enabling both to be worked on at the same time. This proposal combines ICT tools and manipulative materials based on techniques such as Visual Thinking, game-based learning and the digital Quiz, all integrated under a thematic thread that brings together the three techniques of the proposal, which will be key to the understanding of mathematical content in primary education as shown by the results obtained.
Keywords: Enseñanza primaria; Aprendizaje - Juegos; Matemáticas; Visual thinking; game-based learning; Aritmética; Digital Quiz; Educación primaria; TIC